tan 15° tan 25° tan 35° tan 45° tan 55° tan 65° tan 75°
Answers
Answered by
2
Step-by-step explanation:
tan15⋅tan25⋅tan45⋅tan65⋅tan75
=tan15⋅tan45⋅tan75⋅tan25⋅tan65
=tan15⋅tan(60−15)⋅tan(60+15)tan25⋅tan65
=tan(3×15)tan25tan65
=tan45⋅tan25⋅tan65
=tan25⋅tan65
=
cos(25+65)+cos(25−65)
cos(25−65)−cos(25+65)
=
0+cos40
cos40−0
=1
Answered by
2
Your answer is 1
solution;
=>tan15°× tan25°× tan35°×1 (as tan 45°=1)
×tan (90°-35°) × tan (90°-25°) × tan (90°-15°)
now, we know, tan (90°-$)=cot $
=>tan15°× tan25°× tan 35°× cot35°× cot25°× cot15°
we know that tan $× cot $=1
=>(tan15°× cot15°)× (tan25°× cot25°)× (tan35°× cot35°)
=>1×1×1
=>1
hence your answer is 1.
Similar questions
English,
1 month ago
English,
3 months ago
English,
3 months ago
Math,
11 months ago
Social Sciences,
11 months ago